2019
DOI: 10.1002/lsm.23147
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Assisted Control of Epistaxis in Hereditary Hemorrhagic Telangiectasia: A Systematic Review

Abstract: Background and Objectives Hereditary hemorrhagic telangiectasia (HHT), also known as Osler–Weber–Rendu disease, causes recurrent mucous membrane hemorrhage, especially epistaxis. In this systematic review, we discuss the efficacies of the three most common laser photocoagulation treatments for HHT‐related epistaxis. Study Design/Materials and Methods A systematic literature search was conducted in PubMed and MEDLINE from database inception to March 2019. Studies reporting epistaxis outcomes following argon, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 49 publications
0
18
0
5
Order By: Relevance
“…Various surgical treatment methods for epistaxis in HHT patients have been described, including laser photocoagulation, cauterization, septodermoplasty, embolization, and Young's procedure 4 . Specifically, for laser photocoagulation, previous studies have established its efficaciousness in managing and decreasing the severity of epistaxis associated with HHT, while maintaining a strong safety profile 13,17–19 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various surgical treatment methods for epistaxis in HHT patients have been described, including laser photocoagulation, cauterization, septodermoplasty, embolization, and Young's procedure 4 . Specifically, for laser photocoagulation, previous studies have established its efficaciousness in managing and decreasing the severity of epistaxis associated with HHT, while maintaining a strong safety profile 13,17–19 …”
Section: Discussionmentioning
confidence: 99%
“…These findings compliment results of a study by Hunter et al, who reported a significant decrease of ESS by 0.72 from baseline of 7.1 after KTP laser coagulation treatment 18 . A systematic review by Abiri et al noted that intranasal laser photocoagulation was able to reduce both epistaxis intensity and frequency in more than 70% of patients 13 . Together, there exists an important role for laser photocoagulation in the management of epistaxis in HHT, with in‐office therapy being a viable and efficacious option.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diode laser is a commonly used flexible laser in the nose and face and is an excellent haemostatic tool for telangiectasia, arteriovenous malformations and endoscopic laser‐assisted resections of vascular tumours etc . Other types of fibre laser that can be potentially used for the same purpose are Nd: YAG laser therapy and thulium laser, the first already an established tool in haemorrhagic diseases such as Rendu‐Osler‐Weber syndrome and the second more recently tried in flap preparation for anterior skull base surgery…”
Section: Discussionmentioning
confidence: 99%